Conditional deconvolution ща image in the domain of spatial own frequencies (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2009)
Offered methods of the carrying the algorithm restorations by method Conditional deconvolution in the domain of spatial own frequencies